2019
DOI: 10.22146/ae.49014
|View full text |Cite
|
Sign up to set email alerts
|

Competitiveness of Indonesian Crude Coconut Oil Export in Destination Countries

Abstract: This study aims to examine the competitiveness of Indonesian CCO in destination countries and examine what factors influence the competitiveness of Indonesian CCO in destination countries. The analytical methods used in this research were RCA, EPD, and panel data regression analysis. The time period used in this research was 1996 to 2017. The results of the study concluded that Indonesian CCO had competitiveness in the United States, the Netherlands, Malaysia, China, and Singapore. RCA index in each destinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
6
0
3
Order By: Relevance
“…The high contribution of Indonesia's natural rubber demonstrated significant potential to increase its competitiveness in central destination countries. It is closely related to the penetration and expansion of Indonesia's rubber commodity in these five countries (Cvetković & Petrovic-Randelovic, 2017;Yulhar & Darwanto, 2019). The high volume of Indonesia's natural rubber export depicted its high capacity for producing this commodity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high contribution of Indonesia's natural rubber demonstrated significant potential to increase its competitiveness in central destination countries. It is closely related to the penetration and expansion of Indonesia's rubber commodity in these five countries (Cvetković & Petrovic-Randelovic, 2017;Yulhar & Darwanto, 2019). The high volume of Indonesia's natural rubber export depicted its high capacity for producing this commodity.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies investigated factors affecting to NTMs and the competitiveness of agricultural commodities. Several research which utilized the Ordinary Lease Square (OLS model) in Indonesia revealed that export competitiveness was influenced by productivity, the Indonesia's Natural Rubber Productivity and ….. (Prasada and Dhamira) export price of agricultural commodities, and trade openness (Sa'diyah & Darwanto, 2020;Yanita, Napitupulu, & Rahmah, 2019;Yulhar & Darwanto, 2019). Another study on Indonesia's cocoa commodity analyzed using the ECM model discovered that the export competitiveness was affected by the exchange rate, the world price of cocoa, and the export duty (Hapsari & Yuniasih, 2020).…”
Section: And Rural Development Researchmentioning
confidence: 99%
“…Di sisi lain Indonesia juga masih memiliki potensi untuk memperluas jangkauan ekspor dari produk CCO ini. Hal ini diperkuat dengan penelitian yang dilakukan oleh Yulhar & Darwanto (2019) yang mana komoditas CCO Indonesia memiliki keunggulan komparatif yang kuat dan memiliki daya saing terhadap negara tujuan antara lain Amerika, Belanda, Malaysia, China, dan Singapura.…”
Section: Hasil Dan Pembahasan Analisis Rcaunclassified
“…Global pricing changes have a significant impact on the Indonesian market [9]. Indonesian coconut has a very significant comparative advantage, especially given the popularity of its raw coconut [10]. Because of its various advantages, including its processed products that have been exported to numerous foreign nations like Japan, China, Taiwan, and South Korea, the food crop commodity known as porang offers economic prospects [11].…”
Section: Introductionmentioning
confidence: 99%